2019
DOI: 10.5435/jaaos-d-17-00283
|View full text |Cite
|
Sign up to set email alerts
|

Quality Measures in Total Hip and Total Knee Arthroplasty

Abstract: Introduction: Total joint arthroplasty represents the largest expense for a single condition among Medicare beneficiaries. Payment models exist, such as bundled payments, where physicians and hospitals are reimbursed based on providing cost-efficient, high-quality care. There is a need to explicitly define "quality" relevant to hip and knee arthroplasty. Based on prior quality measure research, we hypothesized that less than 20% of developed quality measures are outcome measures. Methods: This study systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…We found fewer quality measures applicable to pediatric orthopaedic surgery compared with other fields of orthopaedic surgery. 12,13,[16][17][18]21 In similar systematic reviews there were 134 measures identified in the field of hand surgery, 116 measures in arthroplasty, 74 measures in spine surgery, and 116 in orthopaedic sports medicine. Similar to other fields of orthopaedic surgery, quality measures in pediatric orthopaedic surgery are unequally represented, with process measures being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…We found fewer quality measures applicable to pediatric orthopaedic surgery compared with other fields of orthopaedic surgery. 12,13,[16][17][18]21 In similar systematic reviews there were 134 measures identified in the field of hand surgery, 116 measures in arthroplasty, 74 measures in spine surgery, and 116 in orthopaedic sports medicine. Similar to other fields of orthopaedic surgery, quality measures in pediatric orthopaedic surgery are unequally represented, with process measures being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome measures are regarded as the most important Donabedian domain, as they measure directly the effect of the intervention on the patient [42]. The identified distribution is, therefore, encouraging, particularly in comparison with other reviews of quality indicators in other surgical fields, which identified most process indicators [43–47]. That said, 26 (38% of all indicators collected) of the outcome indicators were found in a single paper that defined rates of various regional anaesthesia‐related complications as individual outcome indicators [37].…”
Section: Discussionmentioning
confidence: 99%
“…We identified six recent systematic reviews of quality measures in orthopaedic surgery published in the last five years. [2][3][4][5][6][7] The subspecialties investigated include spine, 2 sports medicine, 3 total hip arthroplasty and total knee arthroplasty (THA/TKA), 4 trauma, 5 upper limb, 6 and foot and ankle. 7 These studies highlight that two-thirds of quality measures apply to care processes rather than validated outcome measures or the result of care delivered.…”
Section: Current Orthopaedic Quality Measuresmentioning
confidence: 99%
“…This highlights the uneven representation of quality metrics across process and structure domains and the lack of focus on PROs, which are arguably more relevant in orthopaedics. [2][3][4][5][6][7] Although these published reviews provide a comprehensive list of all available orthopaedic quality metrics, many of the metrics highlighted in these papers are no longer actively in use or have been revoked by the originating agency. A more sustainable approach is to highlight open-access, updated resources that include active quality measures and their utility.…”
Section: Current Orthopaedic Quality Measuresmentioning
confidence: 99%